User Experience Analysis on Facebook Marketplace Pekanbaru using User Experience Questioner Method - Raihan Mukti; Megawati; Angraini; Mona Fronita (P3M Politeknik Negeri Bengkalis, 2025)
The integration of e-commerce features into social media platforms has created unique user experience challenges, particularly in localized buying and selling communities. This study evaluates the user experience of Facebook Marketplace within the Pekanbaru Jual Beli Online (PJBO) community using the User Experience Questionnaire (UEQ) method. Through a quantitative approach with 400 active users selected via simple random sampling, this research reveals significant user experience gaps in a platform that accommodates over 136,000 members. The results demonstrate that four core UX dimensions fall below industry benchmarks: attractiveness (0.85), clarity (0.81), efficiency (0.82), and dependability (0.79), all with narrow confidence intervals (±0.14-0.18), indicating consistent user dissatisfaction across these dimensions. While stimulation (0.80) achieved